La articulación entre enseñanza e investigación del Derecho - Cardinaux, Nancy (2008)
"Originally published in Orler, José and Sebastián Varela (eds.), Methodology of scientific research in the field of Law, La Plata, Editorial de la Universidad de La Plata, 2008."